Documents

Lista 10 - Regra Da Cadeia e Derivação Implícita (Respostas)

Description
Description:
Categories
Published
of 2
All materials on our website are shared by users. If you have any questions about copyright issues, please report us to resolve them. We are always happy to assist you.
Related Documents
Share
Transcript
  Minist´erio da Educa¸c˜ao Universidade Tecnol´ogica Federal do Paran´aDepartamento Acadˆemico de Matem´atica MA72A - C´alculo Diferencial e Integral II Professor Adriano Verd´erio Lista de Exerc´ıcios 10 - Regra da Cadeia e Deriva¸c˜ao Impl´ıcita 1. Use a regra da cadeia para encontrar  dzdt  ou  dwdt  .a)  z   =  x 2 +  y 2 +  xy ,  x  = sen( t ) e  y  =  e t b)  z   =   1 +  x 2 +  y 2 ,  x  = ln( t ) e  y  = cos( t )c)  w  =  xe yz ,  x  =  t 2 ,  y  = 1 − t  e  z   = 1 + 2 t d)  w  = ln   x 2 +  y 2 +  z  2  ,  x  = sen t ,  y  = cos t  e  z   = tan t 2. Use a regra da cadeia para encontrar  ∂z∂s  e  ∂z∂t .a)  z   =  x 2 y 3 ,  x  =  s cos( t ) e  y  =  s sen( t )b)  z   = sen( θ )cos( φ ),  θ  =  st 2 e  φ  =  s 2 t c)  z   =  e ρ cos( θ ),  ρ  =  st  e  θ  = √  s 2 +  t 2 d)  z   = tan  uv  ,  u  = 2 s  + 3 t  e  v  = 3 s − 2 t 3. A imagem da curva  γ  ( t ) = (2 t,t 2 ,z  ( t )) est´a contida no gr´afico de  z   =  f  ( x,y ) com  f  (2 , 1) = 3, f  x (2 , 1) = 1 e  f  y (2 , 1) = − 1. Determine a reta tangente a  γ   no ponto  γ  (1).4. Em cada caso,  y  =  y ( x ) est´a definida implicitamente pela equa¸c˜ao. Encontre  dydx  em termosde  x  e  y .a)  y 3 +  xy  +  x 3 = 4 b)  x 2 y  + sen( y ) =  x 5. Em cada caso,  z   =  z  ( x,y ) est´a definida implicitamente pela equa¸c˜ao. Encontre  ∂z∂x  e  ∂z∂y  emtermos de  x ,  y  e  z  .a)  e x + y + z +  xyz   = 1 b)  x 3 +  y 3 +  z  3 =  x  +  y  +  z  6. Suponha que as fun¸c˜oes diferenci´aveis  y  =  y ( x ) e  z   =  z  ( x ) sejam dadas implicitamente pelosistema   x 2 +  z  2 = 1 y 2 +  z  2 = 1a) Expresse  dydx  e  dzdx  em termos de  x ,  y  e  z  .b) Determine um par de fun¸c˜oes  y  =  y ( x ) e  z   =  z  ( x ) dadas implicitamente pelo sistema.  Respostas 1a)  dzdt  = (2sen( t ) +  e t )cos( t ) + (2 e t + sen( t )) e t 1b)  dzdt  =  ln( t ) − t sen( t )cos( t ) t √  1+ln 2 ( t )+cos 2 ( t ) 1c)  dwdt  =  e 1 − t 1+2 t  2 t −  t 2 1+2 t  −  2 t 2 − 2 t 3 1+4 t +4 t 2  1d)  dwdt  = tan( t )2a)  ∂z∂s  = 5 s 4 sen 3 ( t )cos 2 ( t ) e  ∂z∂t  = 3 s 5 cos 3 ( t )sen 2 ( t ) − 2 s 5 sen 4 ( t )cos( t )2b) ∂z ∂s  =  t 2 cos( st 2 )cos( s 2 t ) − 2 st sen( st 2 )sen( s 2 t ) ∂z ∂t  = 2 st cos( st 2 )cos( s 2 t ) − s 2 sen( st 2 )sen( s 2 t )2c) ∂z ∂s  =  te st cos( √  s 2 +  t 2 ) − s √  s 2 +  t 2 e st sen( √  s 2 +  t 2 ) ∂z ∂t  =  se st cos( √  s 2 +  t 2 ) − t √  s 2 +  t 2 e st sen( √  s 2 +  t 2 )2d)  ∂z∂s  = −  13 t (3 s − 2 t ) 2  sec 2  2 s +3 t 3 s − 2 t   e  ∂z∂t  =  13 s (3 s − 2 t ) 2  sec 2  2 s +3 t 3 s − 2 t  3) A reta tangente ´e: ( x,y,z  ) = (2 , 1 , 3) +  λ (2 , 2 , 0),  λ ∈ R .4a)  dydx  = − y +3 x 2 3 y 2 + x 4b)  dydx  = −  2 xy − 1 x 2 +cos( y ) 5a)  ∂z∂x  = − e x + y + z + yze x + y + z + xy  e  ∂z∂y  = − e x + y + z + xze x + y + z + xy 5b)  ∂z∂x  = − 3 x 2 − 13 z 2 − 1  e  ∂z∂y  = − 3 y 2 − 13 z 2 − 1 6a)  dydx  =  xy  e  dzdx  = − xz 6b)  y  =  x  e  z   = √  1 − x 2
Search
Tags
Related Search
We Need Your Support
Thank you for visiting our website and your interest in our free products and services. We are nonprofit website to share and download documents. To the running of this website, we need your help to support us.

Thanks to everyone for your continued support.

No, Thanks
SAVE OUR EARTH

We need your sign to support Project to invent "SMART AND CONTROLLABLE REFLECTIVE BALLOONS" to cover the Sun and Save Our Earth.

More details...

Sign Now!

We are very appreciated for your Prompt Action!

x